Analisis Yuridis Eksistensi Terhadap Pelayanan Kantor Pertanahan Dalam Pelaksanaan Pendaftaran Tanah - Absi, Warmiyana Zairi; Utoyo, Marsudi (Lex Librum : Jurnal Ilmu Hukum, 2024)
The benefits of the implementation of land registration are enormous both for landowners and for society in general. For landowners, registration provides legal certainty over their ownership, thereby reducing the risk of disputes that may arise later on. With a valid certificate, the landowner has clear legal power to defend his rights. In addition, land certificates can also increase the economic value of the land, as officially registered land usually has a higher selling price than unlisted land. Land registration helps communities and governments manage natural resources better. Development planning, environmental management, and the development of better agricultural policies can be assisted with accurate and up-to-date land registration data. In addition, land registration also helps increase transparency and accountability in land ownership, which can ultimately support social justice in societies.